The "Character Values in Folktales in the Grade IV Indonesian Language Textbook of the Merdeka Curriculum": - - Hadad, Alwi Al; Hikmat, Ade; Syafi’i, Imam (Jurnal Pendidikan Karakter, 2025)
This study aims to analyze character values found in folktales included in the Grade IV Indonesian Language textbook of the Merdeka Curriculum, and to examine the potential of these texts in shaping elementary students' character literacy. This is a qualitative study using content analysis. The primary data are folktales published in textbooks by the Ministry of Education, Culture, Research, and Technology. The results show that folktales are designed to promote literacy and character competencies, highlighting honesty, responsibility, and empathy. The study offers strategic recommendations for teachers to implement contextual learning based on local narrative texts.